The Representation of Social Class Conflicts in Ally Condie’s Matched - Wardani, Dyah Purwita; Ayu Lestari, Vony Rizka (ATAVISME, 2020)
Matched belongs to the dystopian novel, which is popular in the last twenty years. This genre usually satirizes the established state, which controls every part of people’s lives.  Matched talks about how the government control people’s lives led to the social class conflict.  The social class conflict is essential to be discussed because it shows the unequal structure in the established society. The objective of this research is to examine Ally Condie’s Matched by using Stuart Hall’s theory of representation is to find out the class conflict and exposes the critical position of the author. The method used is descriptive qualitative. The analysis technique is to look at the narrative of the figures, Cassia Reyes and Ky Markham, as the reflection of citizen struggle in a totalitarian government called Society. The findings show that Cassia and Ky have to strive in Society because Society perpetuates its power by manipulating politics and exploiting the economy. This research is encouraging the other researchers to examine Matched from different angles, perspectives and theories to complement the findings of this current study.